Exposure to microplastics during early developmental stage: review of current evidence - Amran, Nur Hanisah; Mohamad Zaid, Siti Sarah; Mokhtar, Mohd Helmy; Abd Manaf, Latifah; Othman, Shatrah (Multidisciplinary Digital Publishing Institute, 2022)
In the last few decades, microplastics (MPs) have been among the emerging environmental pollutants that have received serious attention from scientists and the general population due to their wide range of potentially harmful effects on living organisms. MPs may originate from primary sources (micro-sized plastics manufactured on purpose) and secondary sources (breakdown of large plastic items through physical, chemical, and biological processes). Consequently, serious concerns are escalating because MPs can be easily disseminated and contaminate environments, including terrestrial, air, groundwater, marine, and freshwater systems. Furthermore, an exposure to even low doses of MPs during the early developmental stage may induce long-term health effects, even later in life. Accordingly, this study aims to gather the current evidence regarding the effects of MPs exposure on vital body systems, including the digestive, reproductive, central nervous, immune, and circulatory systems, during the early developmental stage. In addition, this study provides essential information about the possible emergence of various diseases later in life (i.e., adulthood).